Evaluation of Clinical Subacromial Impingement Test Positive Patients with Ultrasonographic Subacromial Impingement Test - Yasemin Tombak; Özgür Zeliha Karaahmet (Hitit Medical Journal)

(untitled)
Objective: Knowing which of the special clinical tests used in subacromial impingement syndrome is more successful in making the diagnosis is important for patient evaluation, determining if further examination is necessary, and arranging treatment. Utilizing sonographic impingement as a reference diagnostic technique, the study sought to evaluate how well clinical test results performed in diagnosing patients with subacromial impingement syndrome.Material and method: The study involved 42 patients with shoulder pain and at least one positive subacromial impingement test, including Neer, Hawkins, or Yocum tests. Dynamic sonographic compression of the tendon in the coracoacromial area was examined by abducting the shoulder. Dynamic sonographic compression findings were compared with clinical examination tests.Results: In 40.5% of the patients, the ultrasonographic impingement test was positive. Hawkins test was positive in 81% of patients, Neer test was positive in 69% of patients, and Yocum test was positive in 78.6% of patients. A significant relationship was found between the ultrasonographically evaluated subacromial impingement test and the Neer test, but no significant relationship was found with other special tests (Hawkins and Yocum test) (p = 0.02, p = 0.4, p = 0.12, respectively).Conclusion: We have demonstrated a significant relationship between the ultrasonographic finding of dynamic subacromial impingement and the Neer test, which is a non-invasive and device-independent physical examination test.